Pengaruh Simulasi OSCE terhadap Kesiapan Keterampilan Klinis Mahasiswa Kebidanan: Systematic Literature Review - Dude, Tirsa Aprilia (Cetta: Jurnal Ilmu Pendidikan, 2025)
Midwifery education faces challenges in preparing students for diverse clinical situations, where the gap between theoretical knowledge and practical application becomes a crucial problem affecting the quality of maternal and neonatal healthcare services. This study aims to systematically analyze the effect of OSCE simulation on clinical skills readiness of midwifery students through systematic literature review, with emphasis on the novelty of high-fidelity technology and virtual reality implementation in midwifery OSCE assessment. The research method used systematic literature review with analysis of ten scientific articles consisting of five international journals and five national journals published between 2021-2025, with systematic search through PubMed, ScienceDirect, Google Scholar, Portal Garuda, and DOAJ databases using relevant keywords, then analyzed using thematic analysis and narrative synthesis according to PRISMA guidelines. Findings show that OSCE simulation significantly improves clinical skills readiness of midwifery students, with innovative high-fidelity and virtual reality technologies demonstrating superior effectiveness - VR technology achieving skills improvement up to 27.70%, high-fidelity simulation providing average improvement of 13.89 points, and competency-based simulation showing significant improvement (p < 0.001) with effects lasting up to 6 weeks. The novelty lies in the integration of immersive technologies that transform traditional OSCE assessment into technology-enhanced learning experiences, enabling midwifery students to practice complex obstetric scenarios safely. Clinical skills readiness is measured through four main attributes: professional skills, communication, self-management, and self-confidence. OSCE simulation proves effective in comprehensively improving midwifery students' clinical skills readiness, with implementation recommendations for high-fidelity technology adoption, competency-based approaches, and integrated digital platforms for learning optimization in midwifery education.